Citizen science through a recreational underwater diving project supports the collection of large-scale marine litter data: The Oceania case study - V. Sciutteri; V. Costa; D. Malara; F. Figurella; I. Campbell; E. Deery; T. Romeo; F. Andaloro; P. Consoli (Marine Pollution Bulletin, 2024)

First record of the mesopelagic fish Diaphus dumerilii (Bleeker, 1856) in the Mediterranean Sea - M. Cavallaro; G. Ammendolia; F. Andaloro; P. Battaglia (Marine Biodiversity, 2017)

Fish community in a surf zone of the northern Sicilian coast (Mediterranean Sea): diversity and functional guild composition - V. ESPOSITO; L. CASTRIOTA; P. BATTAGLIA; P. CONSOLI; T. ROMEO; G. SCOTTI; F. ANDALORO (Mediterranean Marine Science, 2015)
Fish assemblage in a surf zone of the southern Tyrrhenian Sea was investigated for the first time. Samples were collected during four surveys by a modified beach-seine, from June 2005 to May 2006. Overall, 42 species belonging to 19 families were recorded. Among them, Sardina pilchardus showed the highest abundance values, while Mugilids (Oedalechilus labeo and Liza aurata) were the most frequently caught species. The fish community was dominated by pelagic and gregarious species using this habitat as a foraging ground and recruitment area. Juveniles and early adults made up the largest proportion of the ichthyofauna. Fishes inhabiting the surf zone were mainly strictly benthic invertebrate feeders and invertivorous/piscivorous fish; strictly planktivorous were represented by few species but strongly dominant in terms of catch per unit effort; strictly piscivorous fish were poorly represented. Fish composition varied over the study period with the greatest abundance in May and December, and the highest richness and diversity in October.

Relationships between otolith size and fish length in some mesopelagic teleosts (Myctophidae, Paralepididae, Phosichthyidae and Stomiidae) - P. Battaglia; D. Malara; G. Ammendolia; T. Romeo; F. Andaloro (Journal of Fish Biology, 2015)
Length–mass relationships and linear regressions are given for otolith size (length and height) and standard length ( L S ) of certain mesopelagic fishes (Myctophidae, Paralepididae, Phosichthyidae and Stomiidae) living in the central Mediterranean Sea. The length–mass relationship showed isometric growth in six species, whereas linear regressions of L S and otolith size fit the data well for all species. These equations represent a useful tool for dietary studies on Mediterranean marine predators.

Concern about the spread of the invader seaweed Caulerpa taxifolia var. distichophylla (Chlorophyta: Caulerpales) towards the West Mediterranean - L. MUSCO; F. ANDALORO; B. MIKAC; S. MIRTO; T. VEGA FERNADEZ; F. BADALAMENTI (Mediterranean Marine Science, 2014)
The new Australian alien seaweed Caulerpa taxifolia var. distichophylla, after being established along the Turkish Mediterranean coast in 2006, was recorded in Southern Sicily in 2007. Since then local fishermen claimed support to counteract the effects of entanglement of large amounts of the alien strain wrack in their trammel nets, causing the gear to become ineffective. The further northward and westward spread of the new alien strain is supposed to be limited by winter temperature. We present novel data confirming that the new alien strain is fully naturalized in Central Mediterranean and is expanding its range beyond such limit (i.e. the 15°C February isotherm), thus becoming potentially able to colonize the western basin. By means of a preliminary estimation of effects on native polychaete assemblages, and considering some peculiarities of Sicily (mostly linked to its geographical position in the Mediterranean Sea), the risk linked to the increasing range of distribution of the invasive algae is highlighted.

Size influences the spatial distribution and fish‐aggregating device use of five Mediterranean fish species - M. SINOPOLI; F. BADALAMENTI; G. D’ANNA; M. GRISTINA; F. ANDALORO (Fisheries Management and Ecology, 2011)
Fish‐aggregating devices are floating objects used worldwide to improve pelagic fishery yield. Fish‐aggregating devices use the natural attraction exerted by floating objects on juveniles and adults of both pelagic and demersal fish. In this study, it was hypothesised that fish change their degree and type of interaction with moored floating objects depending on size. This is because fishes in early life stage remain close to floating objects, using them as a shelter, but as they grow they move further away from floating objects spending their time swimming to seek food. To test this hypothesis, the spatial distribution and habitat use of five Mediterranean fish species were quantified. The results enabled the hypothesis to be accepted for all species, except Balistes carolinensis Gmelin. For this species, a shelter from predator model was applicable, but for the other species, the generalised meeting point model was more adaptable.

Temporal variations in the diet of pearly razorfish Xyrichtys novacula (Osteichthyes: Labridae) - L. Castriota; M. Falautano; M. G. Finoia; D. Campo; M. P. Scarabello; F. Andaloro (Journal of Fish Biology, 2010)
The diet of pearly razorfish Xyrichtys novacula , caught monthly along the shores of the Island of Lampedusa, appeared to be mainly composed of crustaceans, followed by colonial ascidians, molluscs and polychaetes. Among prey, sand dwellers and phanerogam‐associated species were recorded. In winter months, the diet was characterized by a small number of prey items, dominated by colonial ascidians, while in spring and summer a wider prey array was recorded. Dietary indices show that X. novacula do not strictly exploit benthic prey but also pelagic organisms, such as copepods. This feeding behaviour reached its peak in March and October, when the abundance of primary consumers was at its highest after phytoplankton blooms. Furthermore, X. novacula caught prey organisms according to their availability and seasonal patterns during their life cycles, irrespective of fish size.

Bathymetric and longitudinal distribution analyysis of the rockfish Helicolenus Dactylopterus (Delaroche, 1809) in the southern Tyrrhenian Sea (central Mediterranean) - T. ROMEO; L. CASTRIOTA; P. CONSOLI; M. FALAUTANO; G. FLORIO; F. PERDICHIZZI; M.G. FINOIA; F. ANDALORO; P. RINELLI (Mediterranean Marine Science, 2009)
This study provides information on bathymetric and longitudinal distribution heterogeneity of the rockfish Helicolenus dactylopterus in the southern Tyrrhenian Sea. Data were drawn from experimental bottom trawl (1996-2002) plus bottom trap (2001-02) surveys. The frequency of occurrence and mean relative density (N/km2) and biomass (kg/km2) indexes were calculated for two survey seasons (spring and autumn), four geographic sectors and three depth strata. MANOVA was used to test fish abundance among years, sectors and strata. Analysis of the length-frequency distributions was carried out by two-way (gears and depths) ANOVA, post hoc multiple comparisons for testing differences among depths and Student’s t test for testing differences between gears. Length-weight relationship was also estimated and the allometric coefficient was tested with the Student’s t test. The results showed a significant positive bathymetric gradient of sizes both for trawl and trap surveys; at same depths, fish caught by traps were significantly longer than those caught by trawl. In spring surveys, significant differences were found among strata for both abundance indexes; in autumn surveys, significant differences between depth strata were found only for density indices. The distribution and abundance patterns of H. dactylopterus along the southern Tyrrhenian Sea was homogeneous among sectors. Length-weight relationship showed a significant positive allometric growth.

Feeding habits of the albacore tuna Thunnus alalunga (Perciformes, Scombridae) from central Mediterranean Sea - P. Consoli; T. Romeo; P. Battaglia; L. Castriota; V. Esposito; F. Andaloro (Marine Biology, 2008)

FADs influence on settlement and dispersal of the young-of-the-year greater amberjack (Seriola dumerili) - M. Sinopoli; G. D’Anna; F. Badalamenti; F. Andaloro (Marine Biology, 2007)

Annotated list of marine alien species in the Mediterranean with records of the worst invasive species - A. ZENETOS; M.E. CINAR; M.A. PANCUCCI-PAPADOPOULOU; J.G. HARMELIN; G. FURNARI; F. ANDALORO; N. BELLOU; N. STREFTARIS; H. ZIBROWIUS (Mediterranean Marine Science, 2005)
This collaborative effort by many specialists across the Mediterranean presents an updated annotated list of alien marine species in the Mediterranean Sea. Alien species have been grouped into six broad categories namely established, casual, questionable, cryptogenic, excluded and invasive, and presented in lists of major ecofunctional/taxonomic groups. The establishment success within each group is provided while the questionable and excluded records are commented in brief. A total of 963 alien species have been reported from the Mediterranean until December 2005, 218 of which have been classified as excluded (23%) leaving 745 of the recorded species as valid aliens. Of these 385 (52%) are already well established, 262 (35%) are casual records, while 98 species (13%) remain “questionable” records. The species cited in this work belong mostly to zoobenthos and in particular to Mollusca and Crustacea, while Fish and Phytobenthos are the next two groups which prevail among alien biota in the Mediterranean. The available information depends greatly on the taxonomic group examined. Thus, besides the three groups explicitly addressed in the CIESM atlas series (Fish, Decapoda/Crustacea and Mollusca), which are however updated in the present work, Polychaeta, Phytobenthos, Phytoplankton and Zooplankton are also addressed in this study. Among other zoobenthic taxa sufficiently covered in this study are Echinodermata, Sipuncula, Bryozoa and Ascidiacea. On the contrary, taxa such as Foraminifera, Amphipoda and Isopoda, that are not well studied in the Mediterranean, are insufficiently covered. A gap of knowledge is also noticed in Parasites, which, although ubiquitous and pervasive in marine systems, have been relatively unexplored as to their role in marine invasions. Conclusively the lack of funding purely systematic studies in the region has led to underestimation of the number of aliens in the Mediterranean. Emphasis is put on those species that are current or potential threats to the marine ecosystems, namely the Worst Invasive Alien Species providing their record across major groups.

Crustacean fishery with bottom traps in an area of the southern Tyrrhenian Sea: species composition, abundance and biomass - L. CASTRIOTA; M. FALAUTANO; T. ROMEO; J. FLORIO; P. PELUSI; M.G. FINOIA; F. ANDALORO (Mediterranean Marine Science, 2004)
The north-eastern coast of Sicily is characterized by deep, steep bottoms, not easily exploitable by trawl fishery. In this area few fishermen use bottom traps to catch shrimps and Norway lobsters. Our studies were aimed at identifying the species’ composition, abundance and biomass of crustaceans exploitable by bottom traps in this area. Monthly samples over one year were obtained from two lines of 30 baited traps each, at depths between 100 and 500 m. One line was placed in an area usually exploited by this fishery; the other line was used in the unexploited deepest bottoms. Trapped specimens were counted and weighed. ANOVA test, post hoc multiple comparisons and Student’s t test were applied on abundance and biomass data, for testing differences between areas, among seasons and species. During 22 fishing days, 23 species characteristic of the bathyal mud assemblage were caught, 8 of which were not considered commercial. Plesionika edwardsii was the most important species, recorded in the whole bathymetric range investigated; Nephrops norvegicus was significantly higher in terms of biomass in the unexploited area. The discard, of slight importance, was mostly represented by the crab Liocarcinus depurator. Spring season yielded the best catches in both areas, showing the highest values for both abundance and biomass

Reproductive cycle and sex inversion in razor fish, a protogynous labrid in the southern Mediterranean Sea - G. Candi; L. Castriota; F. Andaloro; M. G. Finoia; G. Marino (Journal of Fish Biology, 2004)
The reproductive biology of the Mediterranean razor fish Xyrichthys novacula was investigated by demographic data and histological analysis of the female, intersexual and male gonads. Specimens were collected by bottom trawl on a monthly basis between June 2000 and July 2001 in a sandy bay in southern Thyrrenian. Gonad histology confirmed that the Mediterranean razor fish is a monandric, protogynous hermaphrodite. Females reached first sexual maturity at 100 mm ( L T ) and the estimated mean L T at first maturity ( L 50 ) was 125 mm. Females exhibited asynchronous ovarian development and multiple ovulations occurred over the spawning period. Vitellogenesis started in early May and spawning occurred from late May until late September. Sexual transition involved a large‐scale atresia of all oocyte stages and a massive degeneration of ovarian tissue followed by primordial germ cells proliferation. Sex change began at spawning time (June) but transitional individuals tended to cluster at the end of the reproductive period (September). They accounted for 17·1% of the population sampled and were found in a broad size range (105–150 mm L T ).

First record of Seriola vivoliana Cuvier, 1833 in the Mediterranean - L. Castriota; S. Greco; G. Marino; F. Andaloro (Journal of Fish Biology, 2002)
One specimen of Almaco jack Seriola rivoliana is recorded for the first time in the Mediterranean Sea. It was caught in a purse seine off Lampedusa Island in June 2000 and is listed as a new alien fish from the Atlantic Ocean.

Seriola carpenteri : a new immigrant in the Mediterranean from the Atlantic Ocean - P. Pizzicori; L. Castriota; G. Marino; F. Andaloro (Journal of Fish Biology, 2000)
In September 1997, 148 mature Guinean amberjacks Seriola carpenteri , were caught by purse seine o. Lampedusa Island at 20 m depth, the first record of this Atlantic species in the Mediterranean.

Cytogenetic characterization of the greater amberjack, Seriola dumerili (Pisces: Carangidae), by different staining techniques and fluorescence in situ hybridization - L. Sola; O. Cipelli; E. Gornung; A. R. Rossi; F. Andaloro; D. Crosetti (Marine Biology, 1997)